2019
DOI: 10.1177/0021998318822716
|View full text |Cite
|
Sign up to set email alerts
|

Natural fiber-reinforced high-density polyethylene composite hybridized with ultra-high molecular weight polyethylene

Abstract: A great deal of research and development work has been recently conducted on natural fiber-reinforced polymer matrix composite for its abundancy, low density, excellent damping characteristic, and good mechanical properties. However, the low strength of natural fiber composite has limited its use to only low stress applications. The purpose of this work is to develop a natural fiber hybrid material with both enhanced strength and failure strain using a novel approach and study the effect of the processing temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…UHMWPE fibers have a high level of tensile strength, bending and abrasion, a low-density index, a low degree of swelling, high heat resistance and chemical resistance, biological inertness, high dielectric characteristics, etc. (Lin et al, 2007;Ning., Pillay, Lu, Zainuddin, Yan, 2019;Perepelkin, 2005).…”
Section: Uhmwpe Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…UHMWPE fibers have a high level of tensile strength, bending and abrasion, a low-density index, a low degree of swelling, high heat resistance and chemical resistance, biological inertness, high dielectric characteristics, etc. (Lin et al, 2007;Ning., Pillay, Lu, Zainuddin, Yan, 2019;Perepelkin, 2005).…”
Section: Uhmwpe Fibersmentioning
confidence: 99%
“…To increase the adhesive strength of the polymer-filler system, various methods are used, in particular, there are works on the use of plasma-chemical treatment of fibers with a positive effect. Plasma modification in certain media contributes to an increase in the hydrophilicity of fibers, which accordingly affects an increase in the polymer-filler adhesive interaction with a subsequent increase in the strength parameters of the polymer composite material as a whole (Ning et al, 2019;Perepelkin, 2005). Plasma is capable of changing the surface properties of a material as a result of physical or chemical modification of the outer layer (thickness ≤ 1 μm) without changing the bulk characteristics of the modified materials.…”
Section: Uhmwpe Fibersmentioning
confidence: 99%
“…Despite this benefit, manufacturing of synthetic fiber has a number of drawbacks, including high energy consumption, human health risks, and the accumulation of solid waste due to its non-biodegradable nature. [3][4][5] These disadvantages necessitate the use of plant-based natural fiber reinforced polymer composites in place of synthetic fibers. Plantbased natural fibers are less expensive, environmentally benign, and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…CTPF is primarily constituted of 50.1 wt% cellulose, 24.9 wt% lignin, and 11.9 wt% hemicellulose, with a tensile strength of 184 MPa and a young's modulus of 5.5 GPa. [10][11][12] The fiber's diameter ranges from 380 to 543 μm, with a density of 1.360 g/cm 3 . Since the characteristics are equal to other natural fibers already employed as reinforcement in polymer composites, the crystallinity index of 52% and thermal stability up to 190 C ensures its use as reinforcement in polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Research on HDPE composites has been widely reported with the potential for unique new properties. Ning [23] conducted research on natural fibers from kenaf as HDPE reinforcement. As a result, the tensile strength of kenaf-HDPE composite was 49 MPa.…”
Section: Introductionmentioning
confidence: 99%